Analisis Kebutuhan Pengembangan Modul Pop-Up Book Edukasi Seksualitas Anak Usia Dini untuk Meningkatkan Minat Baca Orang Tua Peserta Didik di Taman Bermain Sahabat Sekar Mekar (TBSSM) - Delly Diana; Aliah Bagus Purwakania Hasan; Fidesrinur (EduInovasi: Journal of Basic Educational Studies, 2025)
The high rate of sexual harassment and violence against children shows the urgency of early childhood sexuality education. Lack of parental understanding of how to convey sexuality information appropriately, coupled with low interest in reading, are the main obstacles in providing effective education. This study aims to develop and test the effectiveness of pop-up book media as an educational tool in conveying sexuality education to early childhood. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were 30 parents and teachers at the Sahabat Sekar Mekar Playground, South Tangerang. Data were collected through questionnaires, in-depth interviews, and documentation. The results showed that the majority of respondents were aware of the importance of sexuality education and felt that pop-up books were an interesting media and helped them in conveying material to children. Pop-up books are considered effective because of their attractive 3D visualization and simple language, which are able to overcome communication barriers between parents and children. However, the main obstacles faced are economic limitations and lack of knowledge about the use of this educational media. These findings indicate that pop-up book media has great potential in supporting early childhood sexuality education, especially if accompanied by socialization and training for parents. Research recommendations include the development of more affordable and relevant pop-up book content, as well as increasing family literacy through visual and narrative approaches.